Hemp seed significantly modulates the endocannabinoidome and produces beneficial metabolic effects with improved intestinal barrier function and decreased inflammation in mice under a high-fat, high-sucrose diet as compared with linseed - Ben Necib, Rim; Manca, Claudia; Lacroix, Sébastien; Martin, Cyril; Flamand, Nicolas; Di Marzo, Vincenzo; Silvestri, Cristoforo (Frontiers in Immunology, 2022)
A diet rich in omega-3 fatty acids supports cardiometabolic health and reduces chronic low-grade inflammation. These fatty acids may impart their health benefits partly by modulating the endocannabinoidome as well as the gut microbiome, both of which are key regulators of metabolism and the inflammatory response. Whole hemp seeds (cannabis sativa) are of exceptional nutritional value, being rich omega-3 fatty acids. We assessed the effects of dietary supplementation of whole hemp seeds in comparison to whole linseeds in a diet-induced obesity mouse model and determined their effects on obesity and the gut microbiome-endocannabinoidome axis. We show that whole linseed supplementation increased weight gain and adiposity in mice, while hemp seeds had no effect. Furthermore, while hemp seeds appeared to be neutral with respect to their effects on glucose handling, linseed supplementation resulted in higher fasting glucose levels and greater levels of insulin release during an oral glucose tolerance test in conjunction with higher levels of liver triglycerides and lower levels of HDL as compared to mice supplemented with hemp seeds. Furthermore, hemp seed supplementation mitigated diet-induced obesity-associated increases in circulating PAI-1 levels, while having no effects on markers of inflammation in epididymal adipose tissue, which were however increased by in mice fed linseeds. Both hemp seeds and linseeds were able to modify the expression of several endocannabinoidome genes in a tissue specific manner in conjunction with markedly increasing the levels of several omega-3 fatty acid-derived endocannabinoidome bioactive lipids with previously suggested anti-inflammatory actions. While neither diet markedly modified the gut microbiome, mice on the hemp seed diet had higher abundance of Clostridiaceae_1 and Rikenellaceae than mice fed linseed or control diets, respectively. Thus, hemp seed-containing foods might represent a source of healthy fats that are not likely to exacerbate the metabolic consequences obesogenic diets whilst producing some anti-inflammatory actions.